Apes, Great Apes, and Mankind in 19th and early 20th Century German Literature - Tanja Nusser (Recherches Germaniques)
Since the Middle Ages, apes have functioned as mirrors of humans. And to this day, we find that especially great apes act as unsettling doubles and distorted images of the human in literature and film, marking the porous border between the animalistic and the human. This article analyzes the depiction of apes in German literature in the 19th and early 20th centuries. It demonstrates that literary texts after Haeckel and Darwin picked up constellations and questions similar to those addressed in earlier texts, especially from the first half of the 19th century: In these texts, we face a human-ape relationship that is imagined as an act of imitation or ‘aping’ (Nachäffen). After a discussion of Darwin and Haeckel, the article will turn to texts by E.T.A Hoffmann, Wilhelm Hauff and Franz Kafka, authors who used images of apes to explore questions of enculturation, the idea of the cultivated human, and the act of imitation as a means to acquire culture.